2021
DOI: 10.1080/10402004.2021.1922790
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Methods for Viscosity Simulations of Lubricants at Different Temperatures and Pressures: A Case Study on PAO-2

Abstract: The behavior of lubricants at operational conditions, such as at high pressures, is a topic of great industrial interest. In particular, viscosity and the viscosity-pressure relation are especially important for applications and their determination by computational simulations is very desirable. In this study we evaluate methods to compute these quantities based on fully atomistic molecular dynamics simulations which are computationally demanding but also have the potential to be most accurate. We used the 9,1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…Molecular dynamics (MD) simulations have been used often for the prediction of thermophysical bulk properties of lubricants, wetting, and interfacial properties on solid walls, as well as for the simulation of tribological contact processes. Simulations of lubricants usually aim at predicting transport properties, in particular the viscosity, using either equilibrium molecular dynamics (EMD) or nonequilibrium molecular dynamics (NEMD) simulations. , Both methods are challenging: EMD simulations require a large computational effort to compute the viscosity, especially for higher viscosities due to the slow convergence of the autocorrelation function (ACF) . In NEMD simulations, the shear rate has to be small enough to reach the Newtonian regime, which can require very long simulation times due to the bad signal-to-noise ratio at small shear rates .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been used often for the prediction of thermophysical bulk properties of lubricants, wetting, and interfacial properties on solid walls, as well as for the simulation of tribological contact processes. Simulations of lubricants usually aim at predicting transport properties, in particular the viscosity, using either equilibrium molecular dynamics (EMD) or nonequilibrium molecular dynamics (NEMD) simulations. , Both methods are challenging: EMD simulations require a large computational effort to compute the viscosity, especially for higher viscosities due to the slow convergence of the autocorrelation function (ACF) . In NEMD simulations, the shear rate has to be small enough to reach the Newtonian regime, which can require very long simulation times due to the bad signal-to-noise ratio at small shear rates .…”
Section: Introductionmentioning
confidence: 99%
“…They show that this coupling increases with the chain length and that the time needed for the Green–Kubo viscosity integral to convergence can be roughly estimated by the rotational relaxation time, which increases with chain length. This finding was also confirmed by other authors. , The effects of temperature, pressure, and other thermodynamic properties on viscosity have been studied by various researchers. Molecular dynamics was employed on different systems including glass, polyethers, ionic liquids, and biolubricants; force field impact was also studied. , Lacks et al showed that, if the simulations sample a phase space local minima, it may lead to having a lower or higher shear rate than expected, and that would influence the value of the viscosity and suggest the importance of averaging over multiple trajectories. This provides a simple yet powerful methodology to solve this problem .…”
Section: Introductionmentioning
confidence: 53%
“… 5 , 6 The effects of temperature, pressure, and other thermodynamic properties on viscosity have been studied by various researchers. 7 13 Molecular dynamics was employed on different systems including glass, polyethers, ionic liquids, and biolubricants; 14 18 force field impact was also studied. 19 , 20 Lacks et al showed that, if the simulations sample a phase space local minima, it may lead to having a lower or higher shear rate than expected, and that would influence the value of the viscosity and suggest the importance of averaging over multiple trajectories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the two EMD approaches, GK is more widely used since it is easy to implement and has been reported to accurately predict viscosity when viscosity is relatively low [64,104]. However, the autocorrelation functions of stress take a long time to converge, especially when the viscosity of the liquids is over 20 mPa•s [105]. In such cases, the Einstein approach is a more computationally efficient and reasonably accurate approach [106,107].…”
Section: Viscositymentioning
confidence: 99%